Breeding potatoes for developing countries using wild tuber bearing Solanum spp. and ploidy manipulations - Ortíz, R.; Iwanaga, Masaru; Peloquin, S.J. (1994)
The use of ploidy manipulations in potato breeding has been successfully applied by breeders at the International Potato Center (CIP) as a tool for germplasm enhancement and for the introduction of desirable genes of wild species into the cultivated gene pool. This methodology consists in reducing the ploidy level using haploids (2n = 2x = 24) and increasing it through the utilization of 2n gametes. It takes advantage of working at the 2x level to develop genotypes which combine multiple pest/disease resistance and a high frequency of 2n gametes. The specific resistances are obtained mainly from wild species. Then, desirable attributes are transferred to the 4x level by unilateral sexual polyploidization (4x x 2x crosses) using first division restitution (FOR) 2n pollen. CIP's work demonstrates that this approach has been very efficient for the transmission of resistance to cyst and root-knot nematodes, bacterial wilt, early blight and potato tuber moth as well as producing high yielding 4x genotypes which also have yield stability over environments. This recently developed germplasm is now available for potato breeders in developing countries who can produce high yielding and resistant 4x clones adapted to the growing conditions of their countries.